Evaluation of the effectiveness of 940nm Diode Laser in second-stage Dental Implant Surgery compared with the Conventional Scalpel Procedure: An in vivo Study - Ra'ed Mohammed Ayoub Al- Delayme; Lutfi Ghulam Awazli (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Background: Modifi cation of the surgical laser technique could make it useful in dental implantology. The incisional mode of the diode laser can be used safely to uncover implants as long as care is taken to  prevent heat conduction from surrounding tissues back into the implant. Purpose: To evaluate the effectiveness of using a 940 nm diode laser in second stage implant surgery compared to a conventional scalpel approach. Material & Methods: This prospective, intra-individual, double-blind, randomi zed controlled trial was carried out in the Iraqi specialized dental implant and cosmetics center. Twenty-one patients, with a total of 112 endossous dental implants, were identifi ed as having Osseo integrated dental implants and who were ready for second stage dental implant surgery were divided into two groups: 1) scalpel exposure and 2) laser exposure using a 940-nm diode laser. Results: The 940 nm diode laser resulted in minimal postoperative pain, decreased edema with less infl ammatory response, enhanced homeostasis, and regular wound healing. The laser treatment also decreased the time required for fi nal impression and improved patient health quality life. Conclusion: The use of a 940 nm diode laser to perform second stage dental implant surgery is effective and can yield better clinical and subjective results compared to the conventional scalpel surgical exposure.